Stent and Stent-Graft Use in Arteriovenous Dialysis Access - McLennan, Gordon (Seminars in Interventional Radiology, 2016)
Dialysis access failure is a major cause of mortality and morbidity among dialysis patients. Preservation of access is critical to maintaining hemostasis, avoiding uremia, and managing the complications of kidney failure. While angioplasty remains the most common method of managing arteriovenous (AV) access stenoses, the use of stents and stent grafts to manage venous stenoses associated with AV access has become more prominent. There have been several prospective randomized trials that have demonstrated the benefit of these devices in maintaining the target lesion patency of the treated areas. In this article, the author reviews the data relating to stent and stent-graft use at the venous anastomosis and outflow veins for pseudoaneurysms of grafts, at the cephalic arch, and for central venous stenoses.
Keywords: AV graft; AV fistula; stent; stent graft; interventional radiology